2016
DOI: 10.1111/dewb.12132
|View full text |Cite
|
Sign up to set email alerts
|

Power Difference and Risk Perception: Mapping Vulnerability within the Decision Process of Pregnant Women towards Clinical Trial Participation in an Urban Middle‐Income Setting

Abstract: To address the burden of maternal morbidity and mortality in low‐ and middle‐income countries (LMICs), research with pregnant women in these settings is increasingly common. Pregnant women in LMIC‐context may experience vulnerability related to giving consent to participate in a clinical trial. To recognize possible layers of vulnerability this study aims to identify factors that influence the decision process towards clinical trial participation of pregnant women in an urban middle‐income setting. This qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 4 publications
0
40
0
3
Order By: Relevance
“…Additional reasons for participation mentioned were: ability to withdraw , advice from physician , community involvement , cultural acceptability , creating a feeling of community , low pressure decision , need for treatment , research involving a non‐invasive procedure , peer enrolment , low perception of risk , result availability , guarantee of confidentiality , being unaware of voluntariness of participation , research outcome, and finally seeing research participation as motivation to avoid risky behaviour .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional reasons for participation mentioned were: ability to withdraw , advice from physician , community involvement , cultural acceptability , creating a feeling of community , low pressure decision , need for treatment , research involving a non‐invasive procedure , peer enrolment , low perception of risk , result availability , guarantee of confidentiality , being unaware of voluntariness of participation , research outcome, and finally seeing research participation as motivation to avoid risky behaviour .…”
Section: Resultsmentioning
confidence: 99%
“…Additional reasons for participation mentioned were: ability to withdraw [91], advice from physician [20,27,77,85], community involvement [34,[61][62][63]66], cultural acceptability [63,91], creating a feeling of community [44], low pressure decision [75], need for treatment [77], research involving a non-invasive procedure [46,81], peer enrolment [33,44,84], low perception of risk [54,70], result availability [20], guarantee of confidentiality [23,33,34,62], being unaware of voluntariness of participation [46], research outcome, [60,62,66,84] and finally seeing research participation as motivation to avoid risky behaviour [59]. The most important reasons for non-participation were safety concerns, inconvenience, stigmatisation, lack of social support, confidentiality concerns, physical pain, efficacy concerns and distrust.…”
Section: Other Reasons For Participationmentioning
confidence: 99%
“…For many participants, trust in the healthcare providers was a significant element in decision-making about research participation. The role of trust regarding research participation has been observed in multiple settings [16,[27][28][29]. In other contexts, it seems that mistrust is a more important element that needs to be addressed in communities where research takes place [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Si plusieurs visions en recherche clinique contribuent à la catégorisation des femmes enceintes comme vulnérables, la plus répandue actuellement serait peut-être celle liée au fait d'un risque possiblement plus élevé lors de leur participation aux processus de recherche [2,3,[11][12][13]. Cette conception de la vulnérabilité répond à la vision internationale de la vulnérabilité liée aux risques potentiels auxquels s'exposent potentiellement les participants.…”
Section: Femmes Enceintes : Participantes Vulnérablesunclassified
“…Le point le plus pertinent étant que les femmes enceintes doivent « être protégées durant la recherche et non pas de la recherche elle-même » [14]. Le statut des femmes enceintes en recherche est qualifié de « vulnérabilité paradoxale » [13] car la majorité des médications prescrites aux femmes durant la grossesse ne sont pas agréées pour être utilisées chez les femmes enceintes [3][4]. Dans certains cas, seul l'état de grossesse induit une iniquité face à la participation potentielle des femmes enceintes à la recherche.…”
Section: Femmes Enceintes : Participantes Vulnérablesunclassified